Education about Controlling Larvae of Mosquitoes in Bontokassi Village, South Sulawesi - Fuad, Mohammad; Aulia, Farikha; Saputri, Eka Ernalifia; Siampa, Imanuelle Tamara Audrey; Hasan, Wahyuni; Rustam, Sitti Nailah; Manyullei, Syamsuar; Saleh, M; Syamsir, Syamsir; Rachmat, Muhammad (Journal of Mestika Nusantara Satu Community Services, 2024)
The government continues to prioritize the Dengue Hemorrhagic Fever (DHF) disease control program due to the high annual prevalence of cases. Bontokassi Village, one of the villages in Takalar Regency that requires education about DHF vector control. The aim of this community service activity is to increase the knowledge of the Bontokassi Village community regarding controlling mosquito larvae, which are disease vectors. Educational activities related to controlling mosquito larvae were carried out at the Integrated Health Post (Posyandu) in Bontokassi Village, South Galesong District, Takalar Regency. The housewives of Bontokassi Village are the target audience for this project. As part of the evaluation procedure, each participant receives a pre-test and a post-test before and after the instructional sessions. The Wilcoxon test results show that there are differences in housewives' knowledge of controlling mosquito larvae, as indicated by the p-value <0.05. This indicates that housewives who took part in teaching and counseling had a greater understanding of controlling mosquito larvae. Conclusion, the knowledge of housewives in Bontokassi Village has increased regarding mosquito larvae control.